2004
DOI: 10.1111/j.1365-246x.2004.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

A deep seismic transect from Hovgård Ridge to northwestern Svalbard across the continental-ocean transition: A sheared margin study

Abstract: S U M M A R YNew seismic refraction data were collected across the western Svalbard continental margin off Kongsfjorden (NyÅlesund) during the cruise leg ARK15/2 of RV Polarstern. The use of onshore and offshore seismic receivers and a dense air-gun shot pattern provide a detailed view of the velocity structure of Svalbard's continental interior, the continent-ocean transition, and oceanic crust related to the northern Knipovich Ridge and the Molloy Ridge.The proposed Caledonian central and western terranes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 50 publications
5
71
0
Order By: Relevance
“…They used a ray tracing model to reproduce the data, and found that crustal thickness varied widely, from 32 km for the continental crust of Svalbard to as little as 2 km (excluding the *2 km of sediment on top of the basement) near the margin between continental and oceanic crust. Mantle velocities are generally [8.0 km/s, but were found to be as low as 7.7 km/s west of Molloy transform fault, where the mantle is likely serpentinized (Ritzmann et al 2004). Also offshore from Svalbard, Geissler and Jokat (2004) Fig.…”
Section: Modeling Methods For Seismic Refraction Datamentioning
confidence: 99%
See 1 more Smart Citation
“…They used a ray tracing model to reproduce the data, and found that crustal thickness varied widely, from 32 km for the continental crust of Svalbard to as little as 2 km (excluding the *2 km of sediment on top of the basement) near the margin between continental and oceanic crust. Mantle velocities are generally [8.0 km/s, but were found to be as low as 7.7 km/s west of Molloy transform fault, where the mantle is likely serpentinized (Ritzmann et al 2004). Also offshore from Svalbard, Geissler and Jokat (2004) Fig.…”
Section: Modeling Methods For Seismic Refraction Datamentioning
confidence: 99%
“…In order to conduct a marine seismic refraction experiment with an offset larger than tens of kilometers, Ritzmann et al (2004) used OBS instruments. They used a ray tracing model to reproduce the data, and found that crustal thickness varied widely, from 32 km for the continental crust of Svalbard to as little as 2 km (excluding the *2 km of sediment on top of the basement) near the margin between continental and oceanic crust.…”
Section: Modeling Methods For Seismic Refraction Datamentioning
confidence: 99%
“…The Norwegian Sea, SW Barents Sea and Svalbard margins are well-studied with extensive deep seismic studies [e.g., Faleide et al, 1991;Mjelde et al, 1997Mjelde et al, , 1998Mjelde et al, , 2002aMjelde et al, , 2005Ritzmann et al, 2002Ritzmann et al, , 2004Breivik et al, 2003Breivik et al, , 2006. In contrast, few deep seismic studies exist across the conjugate NE Greenland margin [Voss and Jokat, 2007;Jokat et al, 2004] and, so far, none to the north of 76°N.…”
Section: Introductionmentioning
confidence: 99%
“…3), and that the 8000 m/s arrival is the result of an interface located substantially below this depth. Energy refracted off an up-dip interface with either serpentenized mantle (with layer velocity ∼7700 m/s; Ritzmann et al, 2004) or lower oceanic crust (velocity ∼7400 m/s; Jones, 1999, p. 342) could produce an apparent velocity of 8000 ± 100 m/s.…”
Section: Deep Structure Across the Continental Shelf And In The Northmentioning
confidence: 99%
“…If the true maximum velocity detected with sonobuoy L14S1 is 7900 m/s (within measurement uncertainty), it is also possible that the interface is in fact the Moho, but is composed of serpentinized mantle such as is observed in the Svalbard continental margin (Ritzmann et al, 2004).…”
Section: Structure Across the Continental Shelf Breakmentioning
confidence: 99%